2008
DOI: 10.1007/s00228-008-0545-z
|View full text |Cite
|
Sign up to set email alerts
|

Limits of add-on trials: antirheumatic drugs

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…Rituximab is a chimeric monoclonal anti-CD20 antibody developed for the treatment of B-cell malignancies. It has been approved for B cell non-Hodgkin lymphoma resistant to other chemotherapy regimens and also in combination with methotrexate in adult patients with moderate to severe active rheumatoid arthritis who have had an inadequate response to one or more TNF antagonist therapies [104,127]. Efficacy of rituximab has also been shown in autoimmune disorders such as systemic lupus erythematosus and pemphigus vulgaris [128][129][130].…”
Section: Targeting Cd20 Cd23mentioning
confidence: 98%
See 1 more Smart Citation
“…Rituximab is a chimeric monoclonal anti-CD20 antibody developed for the treatment of B-cell malignancies. It has been approved for B cell non-Hodgkin lymphoma resistant to other chemotherapy regimens and also in combination with methotrexate in adult patients with moderate to severe active rheumatoid arthritis who have had an inadequate response to one or more TNF antagonist therapies [104,127]. Efficacy of rituximab has also been shown in autoimmune disorders such as systemic lupus erythematosus and pemphigus vulgaris [128][129][130].…”
Section: Targeting Cd20 Cd23mentioning
confidence: 98%
“…Monoclonal antibodies targeting TNFare mostly approved for selected autoimmune inflammatory disorders [102][103][104]. Experimental and clinical studies also suggest that TNF-may play a role in the pathogenesis of asthma [105,106].…”
Section: Targeting Tnf-; Adalimumab Certolizu-mab Pegol Etanerceptmentioning
confidence: 99%
“…Corticosteroids are major active medications used in systemic diseases. However, as a cointervention, their potential effect on the results of parallel-group randomized trials has not been extensively evaluated (2,3,18,19). Our study showed that the between-arm difference in corticosteroid dose may have a clinical impact and may lead to biased interpretation of the results.…”
Section: Discussionmentioning
confidence: 81%
“…Whether the combined prescription of another therapeutic agent (e.g., an immunosuppressant) can further improve patient outcome is evaluated by conducting clinical trials, whereby the treatments being compared are prescribed in addition to corticosteroids (1)(2)(3)(4). Randomization aims to equally balance prior corticosteroid use in each arm at baseline, but corticosteroid dose is highly likely to be modified by physicians throughout the trial, depending on the course of the disease, the effect of the tested intervention, and adverse events (5).…”
Section: Introductionmentioning
confidence: 99%
“…For instance in trials with an add-on design one of the two arms receives the new drug and the other a placebo, while both are given an effective drug that is already available which, as such, cannot be omitted; this is acceptable if there is no previous study showing that another drug has already shown a beneficial effect for the same indication with the same design. The RCTs of new anti-TNFa or other so-called disease modifying anti-rheumatic drugs (DMARD) is paradigmatic: they are added to methotrexate in comparison with placebo even though other drugs are already known to act synergistically with methotrexate [2]. Another example is in diabetes.…”
Section: The Excessive Use Of Placebomentioning
confidence: 99%